TRANSFORMATIONAL LEADERSHIP'S EFFECT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND ORGANIZATIONAL COMMITMENT BY MEDIATION JOB SATISFACTION IN GROUP OF AWARENESS TOUR OF HOME FLOATING BANGSRING UNDERWATER BANYUWANGI (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
This study aims to determine the effect of leadership transformational to organizational citizenship behavior and organizational commitment to mediation and job satisfaction of Group Tourism Awareness (Pokdarwis) Underwater Bangsring Banyuwangi. The respondents numbered 100 members Travel Awareness Group (Pokdarwis) Underwater Bangsring Banyuwangi with the status of permanent members and non-permanent members which have a minimum term of THREE years. The sampling technique using proportional random sampling, and analysis techniques using Structural Equation Modeling (SEM) with the help of AMOS version 21. The program will measure and model analysis proving the hypothesis by testing Standardized regression weight on the output table AMOS program. If there the value estimate of the indicator - an indicator that has a significance level of ≤ 0.05, the indicator can not describe constructs. The results showed that transformational leadership has a positive and significant effect on organizational citizenship behavior, transformational leadership has a positive effect but no significant effect on job satisfaction, transformational leadership has positive and significant impact on organizational commitment, job satisfaction positive and significant effect on organizational citizenship behavior, job satisfaction affects positive but not significant to organizational commitment. Managerial implications of this research are the group leader should evaluate and improve the implementation of transformational leadership to improve the behavior of organizational citizenship behavior and organizational commitment of the members of the Travel Awareness Group (Pokdarwis) Underwater Bangsring Banyuwangi.